The Energy Field of the Pious Bbelievers - Oleiwi Hussein, Sahira; Jawad Abd Alsadah Kadhim, Hanaa (International Journal of Psychosocial Rehabilitation, 2020)
The goal: to elevate the soul to the realm of godliness to obtain the aura. Research importance: The research stopped for a long time at the truth of the pious in the Qur’an text, as he was amazed by the power of the luminous rays emanating from the pious self, which constitutes the person’s aura and what it is from an integrated formation of mind, soul, and body, so that all its energy centers are homogeneous and balanced. The research relied on two forces: First: The attractive force (positive energy) to prevent the wrath of God Almighty. Second: the repulsive force (negative energy) is disobedient. Anchor: The circle is based on the strength of the anchor (the point in the depth) and is able to destroy the repelling force because it possesses a spiritual energy that adheres to what the Holy Qur’an brought about, the Book of God, the Majestic, the Miraculous, which was and still is a pure spring that scholars eagerly respond to, showing the features of its miracles and the beauty of its statement. And certainly to contribute in this regard the sacred honor and a great responsibility, P may choose to circle the spiritual richness of the righteous and measure the energy field they have. The pious believers are slaves of God, obedient to God and His Messenger, and the walkers approach Sharif Mohammadi Almighty (said, "God, the evil of that day and Veronese and pleasure") (human: 11). Piety came in five aspects in the Qur’an text, which gave the pious aura a radiant energy field that can be measured by specialized devices in this field. Research is a guarantee to determine the energetic range of the pious in the Qur’an text.